Beyond The Principal–Agent Dyad: How MCN Governance Structures Shape Social Proof Mechanisms And Monetization Outcomes In Live-Streaming Social Commerce Ecosystems - Corry Patricia Manik; Fadli Fadli; Muhammad Dharma Tuah Putra Nasution (UNIVED Press, 2026)
The proliferation of live-streaming commerce has reconfigured digital marketing landscapes, yet Multi-Channel Networks (MCNs) remain systematically mischaracterized as exploitative intermediaries depleting creator earnings. Drawing upon Agency Theory, Relationship Marketing, and Social Proof Theory, this study develops a conceptual framework theorizing the strategic governance role of MCNs in talent marketing management, emphasizing digital gift distribution optimization and deliberate social proof construction on TikTok. Critically, this study clarifies that agencies receive a 7–15% commission disbursed directly by TikTok a structural arrangement preserving streamer net revenue entirely, contradicting prevailing exploitative narratives. The framework demonstrates that MCNs function as ecosystem catalysts through technical infrastructure provision, algorithmic performance coaching, and incentive-based mechanisms including diamond injection programs that amplify viewer engagement and algorithmic visibility. Agencies further orchestrate social proof dynamics generating self-reinforcing gifting cascades within a symbiotic value co-creation ecosystem. This study contributes to platform governance, algorithmic creator economy, and social commerce intermediation literature by reconceptualizing MCNs as indispensable strategic ecosystem partners.